2021
DOI: 10.1002/smll.202100490
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High‐Quality Freshwater from a Self‐Sustainable Integrated Solar Redox‐Flow Desalination Device

Abstract: As predicted by the International Energy Agency, our planet faces an energy and water crisis in the next 20 years. [1] Human demand for energy and water continues to increase, but the amounts produced are insufficient to meet consumption. [2][3][4][5][6] The ocean is a huge water source, and freshwater can be obtained by salt removal from seawater, which can be performed via two major commercial techniques: thermal distillation and membrane processing. [7][8][9][10][11][12][13][14] The thermal-based desalinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…This salt removal rate is slightly higher, which is higher than that in the previous reports, 53,61 but lower than that using TiO 2 /N719 as a photoanode. 39 It was demonstrated that the technique of employing Bi 2 O 3 /N719 as the photoanode and AC electrode as the intermediate and counter electrodes in this device is successful and that quick salt removal is achievable with the availability of light.…”
Section: Resultsmentioning
confidence: 98%
“…This salt removal rate is slightly higher, which is higher than that in the previous reports, 53,61 but lower than that using TiO 2 /N719 as a photoanode. 39 It was demonstrated that the technique of employing Bi 2 O 3 /N719 as the photoanode and AC electrode as the intermediate and counter electrodes in this device is successful and that quick salt removal is achievable with the availability of light.…”
Section: Resultsmentioning
confidence: 98%
“… a Initial short-circuit current density at illumination intensity of 150 mW (ref ), 153 mW cm –2 (ref ), 108 mW cm –2 (ref ), 140 mW (ref ), and 100 mW cm –2 (this work), respectively. b I 3 – /I – (redox 1) for DSSC and [Fe­(CN) 6 ] 3–/4– (redox 2) for RFD unit. …”
Section: Results and Discussionmentioning
confidence: 99%
“…While previous solar RFD studies demonstrated the feasibility of water desalination driven by sunlight and redox couples, there are some aspects that need further consideration. Either the photocurrent generated in the process was insufficient to produce freshwater, , or an unintegrated DSSC was used to power an RFD system, by externally connecting the two devices. , More importantly, the previously reported systems were operated in a closed-loop mode by recycling the diluate stream several times.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon optimization of PEDOT electrodes grown with different cycles, the electrocatalytic activity is enhanced. Since the PEDOT increased the capacitive behavior, the electrochemically active surface reaction induces the redox reaction of the [Fe­(CN 6 )] 3/4– species , (Figure S2a). The electrocatalytic activity is gradually increased for the PEDOT samples prepared at 5, 10, and 15 cycles.…”
Section: Results and Discussionmentioning
confidence: 99%